Hygiene of food establishments in Southern Minas Gerais (Research, Society and Development, 2025)
The present study aims to evaluate good food production practices in restaurants located in the cities of Alfenas–MG and Carmo do Rio Claro–MG. The research was conducted using a checklist adjusted according to Resolution RDC nº 216/2004 and Resolution RDC nº 275/2002, both from ANVISA (Brazilian Health Regulatory Agency). Six restaurants were evaluated, and the collected data were distributed in graphs for analysis and evaluation. The analysis was divided into three modules: I - Building and Facilities; II - Equipment, Furniture, and Utensils; and III - Food Handlers. For the evaluation of each module, three different options were used: FC (fully complies), PC (partially complies), and NA (not applicable). The establishments were classified as satisfactory approval (76%-100%), regular approval (51%-75%), and disapproval (0%-50%). The results highlight the need for awareness among professionals working in the food sector regarding the importance of adhering to and observing regulations, with the implementation of good manufacturing practices and hygienic-sanitary control, providing a safe and quality food service.